FILM FIKSI TENTANG FENOMENA TOXIC POSITIVITY “BALADA NANDA MENCARI NAMA” - Andi Gita Ardiansyah; I Ketut Buda; Gede Basuyoga Prabhawita (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The film "Balada Nanda Mencari Nama" is a film work that raises the phenomenon of toxic positivity in the community as a topic of discussion in the main problems contained in the film. The realization of the film "Balada Nanda Mencari Nama" was formulated in two problems. The first refers to the concept of the film "Balada Nanda Mencari Nama" which is used in order to visualize the phenomenon of toxic positivity. The second refers to the building element of the film "Balada Nanda Mencari Nama" in order to become a communication medium for the phenomenon of toxic positivity. The design and creation of the film "Balada Nanda Mencari Nama" is based on sources and data collected using qualitative research methodologies with phenomenological approach. The data and information collected have been analyzed with the theory of the form and style of film used as a dissecting the problem. Film form theory discusses the formation of a film "Balada Nanda Mencari Nama" or what is called the concept of a film. Meanwhile, the film style theory contains a system of characteristics from the application of the aspects contained in the film and building a film form. The process of designing the concept of creation based on the research method used, produces a conceptual design and technical depiction of the phenomenon of toxic positivity in the film. The draft concept of the film relates to the use of a film of poetic realism in the film "Balada Nanda Mencari Nama". The technical design of the depiction involves building elements in the film such as mise en scene, cinematography, editing, and sound elements in the film. The technical design of the depiction involving the building elements in the film will be used as a reference in the process of creating the film "Balada Nanda Mencari Nama".